Epidemics and Religion: From Angry Gods and Offended Ancestors to Hungry Ghosts and Hostile Demons - Marshall, Louise (Socio-historical examination of religion and ministry, 2021)
Throughout history, religious beliefs have been a primary way of understanding the experience of epidemic disease. This article offers a pan-historical and cross-cultural analysis of such interactions. The first section examines common structures and assumptions of religious explanatory models. These are characteristically two-fold, nominating both supernatural causal agents and particular human actions that have set these forces in motion. A society’s identification of the behaviors that would prompt the infliction of mass suffering and death upon an entire people reveals a great deal about the values and world view of that culture. Most revolve around definitions of the sacred, which could be polluted, profaned or neglected by deliberate or inadvertent actions, and acceptable standards of moral behavior. Defensive strategies vary according to the nature of the supernatural agency held responsible, from one or more angry gods to offended ancestors, hungry ghosts or hostile demons. The final section investigates the extent to which religion may be helpful or harmful in shaping responses to epidemics, including the present global pandemic of Covid-19.